Regla de 3

Solo disponible en BuenasTareas
  • Páginas : 5 (1016 palabras )
  • Descarga(s) : 0
  • Publicado : 5 de enero de 2011
Leer documento completo
Vista previa del texto
4).

a). Fx=y=5x2

F3=y=532= 45
F2=y=522= 20
F1=y=512= 5
F0=y=502= 0
F-1=y=5-12= 5
F-2=y=5-22= 20
F-3=y=5-32= 45

3 | 2 | 1 | 0 | -1 | -2 | -3 |
45 | 20 | 5 | 0 | 5 | 20 | 45 |

b). Fx=y= -5x2

F3=y=-532= -45
F2=y=-522= -20
F1=y=-512= -5
F0=y=-502= -0
F-1=y=-5-12= -5
F-2=y=-5-22= -20
F-3=y=-5-32= -45

3 | 2 | 1 | 0 |-1 | -2 | -3 |
-45 | -20 | -5 | 0 | -5 | -20 | -45 |

c). Fx=y=(-x)2

F3=y=(-3)2= 9
F2=y=(-2)2= 4
F1=y=(-1)2= 1
F0=y=(0)2= 0
F-1=y=(-(-1))2= 1
F-2=y=(-(-2))2= 4
F-3=y=(-(-3))2= 9

3 | 2 | 1 | 0 | -1 | -2 | -3 |
9 | 4 | 1 | 0 | 1 | 4 | 9 |

d). Fx=y= -(x2)

F3=y=-(3)2= -9
F2=y=-(2)2= -4
F1=y=-(1)2= -1
F0=y=-(0)2= 0F-1=y=-(-1)2= -1
F-2=y=-(-2)2= -4
F-3=y=-(-3)2= -9

3 | 2 | 1 | 0 | -1 | -2 | -3 |
-9 | -4 | -1 | 0 | -1 | -4 | -9 |

e). Fx=y= -(3x3)

F3=y=-333= -81
F2=y=-(3(2)3)= -24
F1=y=-(3(1)3)= -3
F0=y=-(3(0)3)= 0
F-1=y=-(3(-1)3)= 3
F-2=y=-(3(-2)3)= 24
F-3=y=-(3(-3)3)= 81

3 | 2 | 1 | 0 | -1 | -2 | -3 |
-81 | -24 | -3 | 0 | 3 | 24 | 81 |f). Fx=y=(-x)3

F3=y=(-(3))3= -27
F2=y=(-(2))3= -8
F1=y=(-(1))3= -1
F0=y=(0)3= 0
F-1=y=(-(-1))3= 1
F-2=y=(-(-2))3= 8
F-3=y=(-(-3))3= 27

3 | 2 | 1 | 0 | -1 | -2 | -3 |
-27 | -8 | -1 | 0 | 1 | 8 | 27 |

g). Fx=y= -5x3

F3=y= -5(3)3= -135
F2=y= -5(2)3= -40
F1=y= -5(1)3=-5
F0=y= -5(0)3=0
F-1=y= -5-13=5
F-2=y= -5(-2)3=40
F-3=y=-5(-3)3=135

3 | 2 | 1 | 0 | -1 | -2 | -3 |
-135 | -40 | -5 | 0 | 5 | 40 | 135 |

8).

a). Fx=y=2x

F3=y=23=6
F2=y=22=4
F1=y=2=2
F0=y=20=0
F-1=y=2-1=-2
F-2=y=2-2=-4
F-3=y=2-3=-6

3 | 2 | 1 | 0 | -1 | -2 | -3 |
6 | 4 | 2 | 0 | -2 | -4 | -6 |

b). Fx=y=x+5

F3=y=3+5=8
F2=y=2+5=7
F1=y=1+5=6
F0=y=0+5=5
F-1=y=-1+5=4F-2=y=-2+5=3
F-3=y=-3+5=2

3 | 2 | 1 | 0 | -1 | -2 | -3 |
8 | 7 | 6 | 5 | 4 | 3 | 2 |

c). Fx=y=-3x+4

F3=y=-33+4=-5
F2=y=-32+4=-2
F1=y=-31+4=1
F0=y=-30+4=4
F-1=y=-3-1+4=7
F-2=y=-3-2+4=10
F-3=y=-3-3+4=13

3 | 2 | 1 | 0 | -1 | -2 | -3 |
-5 | -2 | 1 | 4 | 7 | 10 | 13 |

d). Fx=y=4-5x

F3=y=4-53=-11
F2=y=4-52=-6
F1=y=4-51=-1F0=y=4-50=4
F-1=y=4-5-1=9
F-2=y=4-5-2=14
F-3=y=4-5-3=19

3 | 2 | 1 | 0 | -1 | -2 | -3 |
-11 | -6 | -1 | 4 | 9 | 14 | 19 |

e). Fx=y=8x-5

F3=y=83-5=19
F2=y=82-5=11
F1=y=81-5=3
F0=y=80-5=-5
F-1=y=8-1-5=-13
F-2=y=8-2-5=-21
F-3=y=8-3-5=-29

3 | 2 | 1 | 0 | -1 | -2 | -3 |
19 | 11 | 3 | -5 | -13 | -21 | -29 |

f). Fx=y=-8x+2F3=y=-83+2=-22
F2=y=-82+2=-14
F1=y=-81+2=-6
F0=y=-80+2=2
F-1=y=-8-1+2=10
F-2=y=-8-2+2=18
F-3=y=-8-3+2=26

3 | 2 | 1 | 0 | -1 | -2 | -3 |
-22 | -14 | -6 | 2 | 10 | 18 | 26 |

6).

a). Fx=y=2x

F3=y=23=6
F2=y=22=4
F1=y=2=2
F0=y=20=0
F-1=y=2-1=-2
F-2=y=2-2=-4
F-3=y=2-3=-6

3 | 2 | 1 | 0 | -1 | -2 | -3 |
6 | 4 | 2 | 0 | -2 |-4 | -6 |

b). Fx=y= -x

F3=y= -3
F2=y=-2
F1=y=2=-1
F0=y=20=0
F-1=y=2-1=1
F-2=y=2-2=2
F-3=y=2-3=3

3 | 2 | 1 | 0 | -1 | -2 | -3 |
-3 | -2 | -1 | 0 | 1 | 2 | 3 |

c). Fx=y=x

F3=y= 3
F2=y=2
F1=y=2=1
F0=y=20=0
F-1=y=2-1=1
F-2=y=2-2=2
F-3=y=2-3=3

3 | 2 | 1 | 0 | -1 | -2 | -3 |
3 | 2 | 1 | 0 | -1 | -2 | -3 |

d).Fx=y=x-2

F3=y=3-2=1
F2=y=2-2=0
F1=y=1-2=-1
F0=y=0-2=-2
F-1=y=-1-2=-3
F-2=y=-2-2=-4
F-3=y=-3-2=-5

3 | 2 | 1 | 0 | -1 | -2 | -3 |
1 | 0 | -1 | -2 | -3 | -4 | -5 |

e). Fx=y=5+x

F3=y=5+3=8
F2=y=5+2=7
F1=y=5+1=6
F0=y=5+0=5
F-1=y=5+-1=4
F-2=y=5+-2=3
F-3=y=5+-3=2

3 | 2 | 1 | 0 | -1 | -2 | -3 |
8 | 7 | 6 | 5 | 4 | 3 | 2 |
tracking img